Combination therapy with 3% diquafosol tetrasodium ophthalmic solution and sodium hyaluronate: an effective therapy for patients with dry eye after femtosecond laser-assisted in situ keratomileusis - Wang, Tianjiao; Di, Yu; Li, Ying (Frontiers in Medicine, 2023)
Purpose: To assess the effect of combination therapy with 3% diquafosol tetrasodium (DQS) and sodium hyaluronate (HA) for dry eye after femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Design: Prospective nonrandomized comparative trial. Methods: The prospective study included 80 eyes of 40 patients who underwent FS-LASIK with or without preoperative dry eye. Patients were divided into a combination group and a HA group according to their willingness and the doctor’s advice. The combination group was treated with DQS six times a day and HA four times a day, and the HA group was treated with HA four times a day after FS-LASIK. Ocular surface disease index (OSDI), ocular symptom score, vision-related score, environmental score, tear meniscus height (TMH), first and average non-invasive tear breakup time (NIBUT-First and NIBUT-Ave), tear breakup time (TBUT), Schirmer I test (SIT), corneal fluorescein staining score (CFS), bulbar and limbal redness scores, lipid layer grade (LLG), meiboscore, lid margin abnormality, corneal sensitivity, and corneal nerve parameters were examined before surgery and at 1 week and 1 month after surgery. Surface regularity index (SRI) was also examined before surgery and at 1 month postoperatively. Results: OSDI score (P=0.024) and vision-related score (P=0.026) were significantly lower in the combination group than in the HA group at 1 month after FS-LASIK, especially in patients with preoperative dry eye symptoms. The increasements of CFS (P=0.018), bulbar redness score (P=0.021), and limbal redness score (P=0.009) were significantly lower in the combination group than in the HA group at 1 week after FS-LASIK. But other ocular surface parameters showed no difference between both groups at 1 week and 1 month after FS-LASIK. LLG was significantly higher in the combination group than in the HA group at 1 week (P=0.004) and 1 month (P<0.001) after surgery, especially in patients with high meiboscore. Regarding the corneal nerve, additional DQS significantly improved nerve fiber density (CNFD) (P=0.038) at 1 month after surgery. Conclusions: The combination therapy with DQS and HA significantly relieved subjective symptoms, improved ocular surface status, and had the potential to promote corneal nerve growth in patients after FS-LASIK.